2023
DOI: 10.1021/acs.analchem.3c02704
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Corrosion Inhibition Behavior of Four Corrosion Inhibitors (BTA, MBI, MBT, and MBO) on Archeological Silver Artifacts Based on Scanning Electrochemical Cell Microscopy

Xiangyu Sun,
Shengyu Liu,
Pei Hu
et al.

Abstract: The problem of corrosion-induced discoloration and embrittlement in silverware is a significant concern for the long-term preservation of excavated archeological silver artifacts, even after thermal restoration. The key to addressing this issue lies in the meticulous selection and evaluation of corrosion inhibitors that possess targeted corrosion inhibition capabilities. This study focuses on the evaluation of corrosion inhibitors for archeological silver artifacts using scanning electrochemical cell microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The widespread use of these substances in the medical field, such as their application as anti-inflammatory [ 2 ], antibacterial [ 3 , 4 ], and antifungal agents [ 5 ], along with their efficacy in treating diseases such as cancer and cardiovascular illnesses [ 6 ], has garnered considerable attention. The interest in this group of compounds arises not only from their medicinal applications but also from their diverse uses in various industries: 2-mercaptobenzothiazole serves as a widely utilized organic corrosion inhibitor [ 7 ] for copper [ 8 , 9 ] and zinc [ 10 , 11 ], and as a component of self-healing and anticorrosion smart coatings [ 12 , 13 , 14 , 15 ]. Larsson et al [ 16 ] suggested that MBT can serve as an additive in dye solar devices.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of these substances in the medical field, such as their application as anti-inflammatory [ 2 ], antibacterial [ 3 , 4 ], and antifungal agents [ 5 ], along with their efficacy in treating diseases such as cancer and cardiovascular illnesses [ 6 ], has garnered considerable attention. The interest in this group of compounds arises not only from their medicinal applications but also from their diverse uses in various industries: 2-mercaptobenzothiazole serves as a widely utilized organic corrosion inhibitor [ 7 ] for copper [ 8 , 9 ] and zinc [ 10 , 11 ], and as a component of self-healing and anticorrosion smart coatings [ 12 , 13 , 14 , 15 ]. Larsson et al [ 16 ] suggested that MBT can serve as an additive in dye solar devices.…”
Section: Introductionmentioning
confidence: 99%